2010
DOI: 10.1016/j.iimb.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Don’t ask, don’t tell: Two views on human resource practices for people with disabilities

Abstract: In the present paper we explore how employees with physical disabilities and their human resource managers perceive practices aimed at entry, integration, and development of disabled employees. The results indicate that both sets of respondents want to treat people with disabilities as 'regular' employees and take attention away from disability. The results also indicate that employees would like to get additional help, but are afraid to ask. Employers do not offer additional support unless asked, not wanting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…Third, there is substantial evidence of widespread discrimination among managers and poor use of HRM by organisations. There is a disconnection between HRM policies and practices and support for employees with disabilities (Kulkarni and Valk 2010). Discrimination in the workplace impacts on employees with a disability through negative employer perceptions, less opportunities for promotion (Schur, Kruse, and Blanck 2005), stricter standards of performance (Graffam et al 2002), forced supervision and failure to appoint due to the disability (Shier, Graham, and Jones 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, there is substantial evidence of widespread discrimination among managers and poor use of HRM by organisations. There is a disconnection between HRM policies and practices and support for employees with disabilities (Kulkarni and Valk 2010). Discrimination in the workplace impacts on employees with a disability through negative employer perceptions, less opportunities for promotion (Schur, Kruse, and Blanck 2005), stricter standards of performance (Graffam et al 2002), forced supervision and failure to appoint due to the disability (Shier, Graham, and Jones 2009).…”
Section: Resultsmentioning
confidence: 99%
“…For example, HR professionals and managers frequently struggle to accommodate and manage the needs of workers with physical disabilities (Kaye, Jans and Jones 2011) and appropriate management support is not always forthcoming (Barlow, Wright, and Wright 2003). The literature identifies a disconnection between HR policies and their implementation in practice (Kulkarni and Valk 2010) and fear of prohibitive costs in making workplace adjustment for workers with disabilities (Lewis, Dobbs, and Biddle 2013;Yang and Konrad 2011). Moreover, evidence suggests that managers and employers more generally have limited understanding or training regarding how to 2002).…”
Section: Management and Employer Knowledge And Support For Workers Wimentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the findings of this study have several implications for rehabilitation counselors. Whether assisting with job search or job retention, counselors must pay careful attention to organizational policies and practices of employers, as they set the standards for employee performance, job task assignment, pay increase and incentives, and training and mentoring opportunities (Kulkarni & Valk, 2010; Stone & Colella, 1996). Subsequently, employees’ self-perception or satisfaction with their own performance depends on the benchmarks set by the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Below I explicate the framework in terms of work unit norms and coworker perceptions—factors that prior research has indicated as being most important in terms of treatment and social integration of PWD in the workplace (Baldridge & Veiga, 2001; Colella, 2001; Colella, Paetzold, Belliveau, & Hollenbeck, 2004; Kulkarni & Lengnick-Hall, 2011; Kulkarni & Valk, 2010; Miller & Werner, 2007; Stone & Colella, 1996). I propose that both work unit norms and coworker perceptions influence help seeking expectancies and behaviors of PWD in the workplace.…”
Section: Overview Of the Frameworkmentioning
confidence: 99%